Knowledge and disposal practises of unused and expired medicines among medical and dental undergraduate students - Shrestha, Binaya; Dixit, Sanjaya Mani (Journal of Kathmandu Medical College, 2022)
Background: Majority of the patients do not consume their medicines exactly as prescribed and thus leave behind unused medicines at the place of stay. The improper disposal of these unused medicines has led to environmental as well as health hazards. Objectives: To assess the knowledge, awareness, and practice of the first and second year medical and dental undergraduates towards the disposal of unused and expired medicines. Methods: This descriptive cross-sectional study was conducted among 206 medical and dental students of a medical college in Kathmandu valley, Nepal. Data were collected by census method from 2022 March to 2022 May after ethical clearance. It was based on an online structured questionnaire to assess the knowledge, awareness, and practice about the disposal of leftover medications. Data analysis was done using Microsoft Excel 2016. Results: A total of 206 students participated in the study of which 161 (78.2%) were from MBBS and 45 (21.8%) from BDS stream. It was noted that 118 (57.3%) students obtained their medicines on prescription, 76 (37.1%) directly from the counter, and 11 (5.3%) obtained from their friends or relatives. Majority (179, 86.9%) of the students checked the expiry date before buying the medicines, 134 (65%) students were aware about the harmful consequences of inappropriate disposal of medicines on health and environment. Conclusion: Proper knowledge on disposal practises of unused and expired medicines among medical and dental students’ needs much improvement. Educational interventions may help improve awareness of proper methods of medicine disposal.